Empowering PKK Women in Household Waste Processing Effort to Reduce Waste and Improve The Quality of Life for the Community - Masud Hermansyah; Ahmad Taufiqurrahman; Suibatul Islamiyah; Mutiara Ikamelia; Muhammad Daniel Thoriq (Medikun Publisher, 2024)
Kuliah Kerja Nyata (KKN) is an important element in higher education that aims to connect students with society and introduce them to real problems faced by society. Tanjungsari Village is one of the villages in the Umbulsari District, Jember Regency. PKK women in Tanjungsari Village have a crucial position as drivers of change at the community level. The form of service activities is carried out by means of socialization and training. The stages of community service activities consist of three stages, namely: preparation, implementation of training, and evaluation. The main objective of the program to empower PKK women in managing waste in Tanjungsari Village is to reduce the volume of waste generated by the community. Through educational and training activities, they are provided with an understanding of the importance of separating waste, waste composition, and effective ways of recycling. By supporting this behavior change, the community can contribute to reducing the negative impact of waste on the environment. In addition to environmental impacts, this empowerment also has the potential to improve the community's economy